Mission-Driven Organizations in Japan: Management Philosophy and Individual Outcomes - Wang, Yingyan (2011)
Previous studies imply that management philosophy has become an essential ethical foundation for a number of mission-driven organizations in Japan. This study examines how management philosophy might be influential to individuals with a sample of 1019 Japanese employees. The article develops a framework for analyzing the adoption of management philosophy and individual attitudinal and behavioral outcomes. Factor analysis shows that adoption of the management philosophy can be categorized into two dimensions, identification with management philosophy, and sensemaking of that management philosophy. Regression results indicate that while philosophy-oriented practice might affect individual adoption of management philosophy, the adoption of the management philosophy is positively related to both job involvement and organizational citizenship behavior. Furthermore, the results of structural equation analysis indicate that both dimensions of the adoption of the management philosophy might mediate the relationship between organizational practice and individual outcomes. The research not only increases our understandings into the effectiveness of the management philosophy as an essential ethical foundation, but also provides intriguing implication regarding the organizational measures required to enhance the mission-driven culture.
Keywords: Organizational Citizenship Behavior; Job involvement; individual outcomes; Sensemaking; Identification; mission-driven organization; management philosophy